2021
DOI: 10.1002/ange.202102466
|View full text |Cite
|
Sign up to set email alerts
|

Efficient (>20 %) and Stable All‐Inorganic Cesium Lead Triiodide Solar Cell Enabled by Thiocyanate Molten Salts

Abstract: Besides widely used surface passivation, engineering the film crystallization is an important and more fundamental route to improve the performance of all-inorganic perovskite solar cells.H erein, we have developed au rea-ammonium thiocyanate (UAT)m olten salt modification strategy to fully release and exploit coordination activities of SCN À to deposit high-quality CsPbI 3 film for efficient and stable all-inorganic solar cells.T he UATi sd erived by the hydrogen bond interactions between urea and NH 4 + from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Recently, exciting results have been achieved for the PCEs of all inorganic CsPbI 3 based PSCs, which exceed 20%. One study for CsPbI 3 PSCs reported that the crystal quality of the CsPbI 3 film was considerably ameliorated by the modification of urea-ammonium thiocyanate (UAT) molten salt, giving rise to a long single-exponential charge recombination lifetime over 30 ns and an encouraging PCE over 20% . The UAT includes a weak Coulombic bonding between NH 4 + and SCN – due to the hydrogen bond interactions between urea and NH 4 + , favoring the coordination of SCN – to the Pb–I octahedrons and thus reducing defects and recombination.…”
Section: Ion Engineeringmentioning
confidence: 99%
“…Recently, exciting results have been achieved for the PCEs of all inorganic CsPbI 3 based PSCs, which exceed 20%. One study for CsPbI 3 PSCs reported that the crystal quality of the CsPbI 3 film was considerably ameliorated by the modification of urea-ammonium thiocyanate (UAT) molten salt, giving rise to a long single-exponential charge recombination lifetime over 30 ns and an encouraging PCE over 20% . The UAT includes a weak Coulombic bonding between NH 4 + and SCN – due to the hydrogen bond interactions between urea and NH 4 + , favoring the coordination of SCN – to the Pb–I octahedrons and thus reducing defects and recombination.…”
Section: Ion Engineeringmentioning
confidence: 99%
“…All-inorganic perovskite CsPbX 3 (X = Cl, Br, I) quantum dots have attracted significant attention of researchers due to their excellent photoelectric performance and outstanding thermal stability in recent years, and perovskite solar cells (PSCs) based on cubic-phase (α) CsPbI 3 have achieved excellent efficiency beyond 20% . Although the power conversion efficiency (PCE) of bulk CsPbI 3 PSCs is close to that of organic–inorganic PSCs (25.6%), bulk CsPbI 3 only maintains the α phase above 310 °C because the size of the Cs cation is too small to match the [PbX 6 ] 4– octahedron, and it transforms into a nonperovskite orthorhombic phase (δ), which is undesirable for photovoltaic applications .…”
Section: Introductionmentioning
confidence: 99%
“…There is a weak Coulomb force between GuaSCN and perovskite. 40 When the annealing temperature exceeds the boiling point of GuaSCN, it volatilizes from the film. This process is conducive to the formation of the (100) and (200) orientations of CsPbIBr 2 grains, 18,21 according with XRD characterization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This suggests that the surface states of the perovskite films have changed. There is a weak Coulomb force between GuaSCN and perovskite . When the annealing temperature exceeds the boiling point of GuaSCN, it volatilizes from the film.…”
Section: Results and Discussionmentioning
confidence: 99%